Influence of water absorption in mechanical properties of natural fibres from kenaf unsaturated polyester composites - Rashdi, Abdalla A. Ab.; Salit, Mohd Sapuan; Megat Ahmad, Megat Mohamad Hamdan; Abdan, Khalina (2009)
Fibre reinforced composites have been gaining wide use in the variety of applications. The performance of these composites may suffer when the material is exposed to adverse environments for long periods of time. Kenaf fibre reinforced unsaturated polyester composites were subjected to water immersion tests in order to study the effects of water absorption on the mechanical properties. Composites specimens containing (10%, 20% and 30%) weight percentage of fibre were prepared. Water absorption tests were conducted by immersing specimens in a distilled water bath at 25oC for four months. The tensile properties of water immersed specimens were evaluated and compared alongside dry composite specimens. A decrease in tensile properties of the composites was demonstrated, showing a great loss in mechanical properties of the water-saturated samples compared to the dry samples. The percentage of moisture uptake increased as the weight percentage of fibre increased due to the high cellulose content. The water absorption pattern of these composites was found to follow Fickian behavior.